Historical Review of Teacher Education in the Inuit Jurisdictions of Canada - McGregor, Heather E.; McGregor, Catherine A. (Unpublished, 2023)
This is a 96 page report. This report provides historical context for the development and offerings of teacher education programs serving Inuit communities in the four Inuit Nunangat (homelands) in Canada. From west to east, they are: Inuvialuit Settlement Region, Nunavut, Nunavik and Nunatsiavut. This report was designed to leverage publicly-available, document-based evidence associated with the history of Inuit teacher education. Each chapter is focused on a different jurisdiction, and constructed to reflect the unique histories of the corresponding jurisdiction. Therefore the length and topics in each chapter vary according to the number of changes to teacher training, or extent of previous research or program reviews conducted in each place. Even though teacher education is the most consistently delivered adult professional program in the North, stakeholders have constantly been dissatisfied with teacher education. In some jurisdictions recommendations for improvement are repeated over and over, and are slow to be implemented, if at all. The report concludes with some strengths and challenges of Inuit teacher education which are drawn from this historical context and which may inform future research.